Harmonious leadership : how to avoid the global catastrophe - Srića, Velimir (Algora Publishing, 2014)
Each one of us is, in a sense, a leader in this world, and the author encourages us to adopt a model of harmony-based leadership. In easily-digested ''lessons'' Prof. Srica gives fifty-two examples explaining in detail how each of us can develop internal harmony, and how to build and develop harmonious teams and organizations. Prof. Srica finds the source of today''s global chaos in the lack of leadership in politics and business, and he explains why the current paradigm is exhausted. The first pages are valuable in their own right, as they present an ice-bath of cold facts that will wake up a.